Electrochemical characterisation of bis(1,10-phenanthroline) gadolinium (III) trichloride formed in situ - MONZON, LORENA (My University, 2010)
The in situ formation and electrochemical behaviour of a complex between Gadolinium (III) and 1,10-phenanthroline (phen) are discussed. The electron withdrawing ability of phen decreases the redox potential of Gd(III). A cathodic peak at -1.7 V vs. Ag/Ag+ 10mM, corresponds to an irreversible electron transfer reaction involving the exchange of two electrons, where the first charge transfer reaction is the rate-determining step. The diffusion coefficient and the total number of electrons were derived using the Shoup-Zsabo equation. Kinetic parameters such us k0, ? and i0 are calculated. Voltammetric simulations are carried out to evaluate the accuracy of the results. A fast chemical reaction consumes the reduced species formed at -1.7 V, which is then oxidised at -0.1 V. The stoichiometry of the complex is determined by the Yoe and Jones? method. An average value for the stability constant of the complex of (2.3 ? 0.8) 105 M-2 is obtained.
PUBLISHED
Keywords: Physics; Gadolinium; Nanoscience & Materials